Question
upstudy study bank question image url

Find the orthogonal projection of \( \mathbf{v}=\left[\begin{array}{c}-11 \\ -13 \\ 1\end{array}\right] \) onto the subspace \( V \) of \( \mathbb{R}^{3} \) spanned by \( \left[\begin{array}{c}3 \\ -4 \\ -1\end{array}\right] \) and \( \left[\begin{array}{c}-2 \\ -4 \\ -2\end{array}\right] \). \( \operatorname{proj}_{v}(\mathbf{v})=\left[\begin{array}{c}\square \\ \hline\end{array}\right] \)

Ask by Fleming Colon. in the United States
Feb 23,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The orthogonal projection of \( \mathbf{v} = \left[\begin{array}{c}-11 \\ -13 \\ 1\end{array}\right] \) onto the subspace \( V \) is \( \left[\begin{array}{c}-\frac{48}{5} \\ -\frac{51}{5} \\ -6\end{array}\right] \).

Solution

We wish to find the orthogonal projection of   v = [–11, –13, 1]ᵀ onto the subspace V ⊆ ℝ³ spanned by   u₁ = [3, –4, –1]ᵀ  and  u₂ = [–2, –4, –2]ᵀ. One way to do this is to express the projection as   p = αu₁ + βu₂ and then choose α and β so that the error vector (v – p) is orthogonal to V. That is, we require   (v – p) · u₁ = 0  and  (v – p) · u₂ = 0. Step 1. Compute the Necessary Dot Products First, compute the inner products of u₁ and u₂ with themselves and with each other:   u₁ · u₁ = 3² + (–4)² + (–1)² = 9 + 16 + 1 = 26   u₂ · u₂ = (–2)² + (–4)² + (–2)² = 4 + 16 + 4 = 24   u₁ · u₂ = 3·(–2) + (–4)·(–4) + (–1)·(–2) = –6 + 16 + 2 = 12 Next, compute the dot products of v with u₁ and u₂:   v · u₁ = (–11)(3) + (–13)(–4) + (1)(–1)       = –33 + 52 – 1 = 18   v · u₂ = (–11)(–2) + (–13)(–4) + (1)(–2)       = 22 + 52 – 2 = 72 Step 2. Set Up the Equations Since   (v – (αu₁ + βu₂)) · u₁ = 0  and  (v – (αu₁ + βu₂)) · u₂ = 0, we have   v · u₁ – α(u₁ · u₁) – β(u₁ · u₂) = 0  →  18 – 26α – 12β = 0  (1)   v · u₂ – α(u₁ · u₂) – β(u₂ · u₂) = 0  →  72 – 12α – 24β = 0  (2) Rewriting the equations:   26α + 12β = 18    (1)   12α + 24β = 72    (2) Step 3. Solve the System for α and β From (2), divide by 12:   α + 2β = 6    →  α = 6 – 2β  (3) Substitute (3) into (1):   26(6 – 2β) + 12β = 18   156 – 52β + 12β = 18   156 – 40β = 18   –40β = 18 – 156 = –138   β = (–138)/(–40) = 138/40 = 69/20 Now substitute back into (3):   α = 6 – 2(69/20) = 6 – 138/20 = 6 – 6.9 = –0.9   In fraction form: 6 = 120/20, so   α = (120/20 – 138/20) = –18/20 = –9/10 Step 4. Write the Projection p The projection is   p = αu₁ + βu₂    = (–9/10)[3, –4, –1]ᵀ + (69/20)[–2, –4, –2]ᵀ Now, calculate each coordinate: • First coordinate:   p₁ = (–9/10)*3 + (69/20)*(–2) = –27/10 – 138/20       = (–54/20 – 138/20) = –192/20 = –48/5 • Second coordinate:   p₂ = (–9/10)*(–4) + (69/20)*(–4) = 36/10 – 276/20       = (18/5 – 69/5) = –51/5 • Third coordinate:   p₃ = (–9/10)*(–1) + (69/20)*(–2) = 9/10 – 138/20       = (9/10 – 69/10) = –60/10 = –6 Thus, the orthogonal projection of v onto V is   proj_V(v) = [ –48/5, –51/5, –6 ]ᵀ. You can now fill in the answer as:   proj_V(v) = [ –48/5; –51/5; –6 ].

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the orthogonal projection of \( \mathbf{v} = \begin{bmatrix} -11 \\ -13 \\ 1 \end{bmatrix} \) onto the subspace \( V \) spanned by the vectors \( \mathbf{u_1} = \begin{bmatrix} 3 \\ -4 \\ -1 \end{bmatrix} \) and \( \mathbf{u_2} = \begin{bmatrix} -2 \\ -4 \\ -2 \end{bmatrix} \), we first need to check if these two vectors are linearly independent. 1. **Checking Linear Independence**: To see if \( \mathbf{u_1} \) and \( \mathbf{u_2} \) are independent, we can find a scalar \( k \) such that \( k \mathbf{u_1} = \mathbf{u_2} \): \[ k \begin{bmatrix} 3 \\ -4 \\ -1 \end{bmatrix} = \begin{bmatrix} -2 \\ -4 \\ -2 \end{bmatrix} \] This gives: \[ 3k = -2 \quad \Rightarrow \quad k = -\frac{2}{3} \] Now check the other components: \[ -4k = -4 \quad \Rightarrow \quad k = 1 \quad (\text{which is inconsistent}) \] Hence, \( \mathbf{u_1} \) and \( \mathbf{u_2} \) are linearly independent. 2. **Finding the Orthonormal Basis**: We can use the Gram-Schmidt process: - Let \( \mathbf{e_1} = \mathbf{u_1} = \begin{bmatrix} 3 \\ -4 \\ -1 \end{bmatrix} \). - To find \( \mathbf{e_2} \), we need to make \( \mathbf{u_2} \) orthogonal to \( \mathbf{e_1} \): \[ \mathbf{e_2} = \mathbf{u_2} - \operatorname{proj}_{\mathbf{e_1}}(\mathbf{u_2}) = \mathbf{u_2} - \frac{\mathbf{u_2} \cdot \mathbf{e_1}}{\mathbf{e_1} \cdot \mathbf{e_1}} \mathbf{e_1} \] First calculate the dot products: \[ \mathbf{u_2} \cdot \mathbf{e_1} = (-2)(3) + (-4)(-4) + (-2)(-1) = -6 + 16 + 2 = 12 \] \[ \mathbf{e_1} \cdot \mathbf{e_1} = 3^2 + (-4)^2 + (-1)^2 = 9 + 16 + 1 = 26 \] So, \[ \operatorname{proj}_{\mathbf{e_1}}(\mathbf{u_2}) = \frac{12}{26} \begin{bmatrix} 3 \\ -4 \\ -1 \end{bmatrix} = \frac{6}{13} \begin{bmatrix} 3 \\ -4 \\ -1 \end{bmatrix} = \begin{bmatrix} \frac{18}{13} \\ -\frac{24}{13} \\ -\frac{6}{13} \end{bmatrix} \] Then, \[ \mathbf{e_2} = \begin{bmatrix} -2 \\ -4 \\ -2 \end{bmatrix} - \begin{bmatrix} \frac{18}{13} \\ -\frac{24}{13} \\ -\frac{6}{13} \end{bmatrix} = \begin{bmatrix} -2 - \frac{18}{13} \\ -4 + \frac{24}{13} \\ -2 + \frac{6}{13} \end{bmatrix} \] Now compute each component: \[ = \begin{bmatrix} -\frac{26}{13} - \frac{18}{13} \\ -\frac{52}{13} + \frac{24}{13} \\ -\frac{26}{13} + \frac{6}{13} \end{bmatrix} = \begin{bmatrix} -\frac{44}{13} \\ -\frac{28}{13}

Related Questions

Latest Other Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy